PENGARUH PEMAHAMAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus Wajib Pajak Kendaraan Bermotor Di Samsat Polda Jakarta Timur) - Ferdinandus Kusuma (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The purpose of this study was to determine the effect of formal taxpayer knowledge and awareness of taxpayers on motor vehicle taxpayer compliance in companies in the area, SAMSAT POLDA East Jakarta. The data used are primary data by distributing questionnaires to Motor Vehicle Taxpayers registered at the SAMSAT POLDA East Jakarta Office. The population that will be the object of research is all motorized taxpayers registered at SAMSAT POLDA East Jakarta Office until the period of December 2016. The sampling technique used is accidental sampling. This study uses a method of linear regression analysis. The results showed that from the understanding of the taxpayer does not have a significant positive effect on motor vehicle taxpayer compliance and taxation sanctions have a significant positive effect on motor vehicle taxpayer compliance.